The impact mechanism of media use on the green and low carbon consumption behavior of China: integrating planned behavior theory and social cognitive theory - Chuang Li; Siting Ruan; Yating Niu; Liping Wang (Scientific Reports)
Abstract As a crucial medium for information dissemination and public opinion guidance, how to leverage media to promote the development of public green and low-carbon consumption (GLC) is a major challenge in the new era. This study, based on the Theory of Planned Behavior and Social Cognitive Theory, employs PLS-SEM and MGA methods to construct a model encompassing traditional media, online media, and social media channels, delving into the relationship between media use (MU) and GLC. The findings indicate that media usage is positively correlated with both aspects of GLC: green and low-carbon consumption intention, green and low-carbon consumption behavior. The order of correlation strength is social media > traditional media > online media. Further mechanistic analysis indicates that green and low-carbon knowledge and social norms mediate the relationship between MU and GLC. Additionally, there are differences in the correlation between MU and GLC among populations with varying levels of media trust and media use frequency. This study provides theoretical and quantitative guidance for leveraging traditional media, online media, and social media to promote GLC among the Chinese public.